Biological control : (Cambridge University Press, 1995)
This book consists of 28 papers are from an international gathering in Saariselka, Finnish Lapland, in March 1992. The book describes the amazing successes of biological control of insects, plant pathogens, and weeds in agriculture and forestry with virtually no documented side effects, and the risks associated with introducing foreign or genetically altered organisms into an environment. It also covers the biological invasions that cause the problem, classical and augmentative biocontrol, the use of genetically modified organisms, and economics and registration.